EFFECT OF AUDIT EXPERTISE, COMPLIANCE PRESSURE, TASK COMPLEXITY, AND EXPERIENCE ON AUDIT JUDGEMENT - Ice Nasyrah Noor; Eka Pujianthi; Meuthia Hamun (Universitas Muhammadiyah Kendari, 2019)
This study aims to analyze the effect of audit expertise, compliance pressure, task complexity, and experience on audit judgment. Sampling techniques use in this research is convenience sampling. The sample in this study are 93 respondents in several Public Accounting Firm in Special Capital Region of Jakarta area. This research is using the test of validity, reliability test, multiple linear regression test, F test, and also t-test. Based on the results of the study, shows that the audit expertise, compliance pressure, task complexity, and experience have a positive effect on auditor judgment.